Thinking gender, doing gender : feminist scholarship and practice today - Rege, Sharmila; Chakravarti, Uma
Contributed
Copyright: Indian Institute of Advanced Study, Shimla.
"Book is a celebration of the spirit of Sharmila Rege and the wide range of interests that she had in the fields of pedagogy, history, and cultural practice'--preface.
Includes bibliographical references and index.
Keywords: Women's studies -- India -- Congresses; Feminism and education -- India -- Congresses